PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK ONLINE DI SHOPEE PADA KARYAWAN DI KOTA BATAM - Crismeny Witaloca Purba; Heryenzus Heryenzus (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
The purpose of this study was to determine the effect of Brand Image and Price on Purchase Decisions on Shopee consumers in Batam City, both partially and simultaneously. The sampling method in this research is using descriptive quantitative methods. Sampling with probability sampling method with the type of simple random sampling. The data collection technique used a questionnaire instrument as many as 100 respondents. The data analysis technique used multiple linear regression. Tests in this study using SPSS 25. Hypothesis testing in this study using t test and f test. The coefficient of determination (R2) obtained from the brand image and price variables on purchasing decisions is 0.792 (79.2%). The results of multiple linear regression indicate that brand image has an effect of 0.377 (37.7%) on purchasing decisions and price has an effect of 0.409 (40.9%) on purchasing decisions. It can be said that from the t test and f test, brand image and price have a significant partial effect on purchasing decisions and brand image and price together have a significant simultaneous effect on purchasing decisions on Shopee.